Bibliometric Analysis of Human Resource Management Research in Islamic-Based Hospitals (2014-2023): Analisis Bibliometrik Penelitian Manajemen Sumber Daya Manusia di Rumah Sakit Berbasis Islam (2014-2023) - Hariyadi, Ilham; Aini, Qurratul (Indonesian Journal of Innovation Studies, 2024)
General Background: Human Resource Management (HRM) is vital for achieving organizational goals, particularly in hospitals where it influences healthcare quality. Specific Background: In Islamic-based hospitals, HRM must align with Islamic values, adding complexity to management practices. Knowledge Gap: There is a lack of bibliometric analysis on HRM research in these hospitals. Aims: This study aims to assess HRM research in Islamic hospitals from 2014 to 2023, identify trends, and highlight research gaps. Results: Research in this area increased notably between 2020 and 2023, with the United States leading. Key themes included hospital management, employee satisfaction, and organizational efficiency. Novelty: This is the first bibliometric analysis of HRM in Islamic-based hospitals. Implications: The findings suggest the need for more research on HRM strategies rooted in Islamic values to enhance hospital performance and healthcare quality. Highlights: Significant increase in HRM research publications in Islamic hospitals from 2014 to 2023. The United States contributed the most research on HRM in Islamic hospitals. Key themes included employee satisfaction, hospital management, and organizational efficiency. Keywords: Human Resource Management, Islamic Hospitals, Bibliometric Analysis, Healthcare Quality, Organizational Performance